2022
DOI: 10.3390/ani12131734
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Natural Transmission of Bovine Leukemia Virus in Dairies from Southern Chile

Abstract: Bovine leukemia virus (BLV) is a retrovirus that affects cattle worldwide. A longitudinal study was conducted with the aim to (a) estimate the incidence rate of the BLV infection of dairy farms in the regions of Los Ríos and Los Lagos (Chile), and (b) describe the frequency and epidemiological association of risk management practices related to new cases in cattle on dairy farms in Southern Chile. Infection status was based on commercial blocking ELISA results, on serum and milk. Individual information on anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
6
0
1
Order By: Relevance
“…A presença do vírus foi identificada no sêmen (31,32) ; no entanto, outros estudos relataram a ausência do vírus no sêmen de animais positivos (33) , bem como baixa transmissão viral pelo sêmen (34) . No Chile, a presença da doença foi associada à inseminação artificial (35) ; os autores afirmam que procedimentos envolvendo inseminação artificial, como palpação retal e contaminação por luvas, podem transmitir altas cargas virais pela mucosa retal. A monta natural foi um fator de proteção neste estudo.…”
Section: Discussionunclassified
“…A presença do vírus foi identificada no sêmen (31,32) ; no entanto, outros estudos relataram a ausência do vírus no sêmen de animais positivos (33) , bem como baixa transmissão viral pelo sêmen (34) . No Chile, a presença da doença foi associada à inseminação artificial (35) ; os autores afirmam que procedimentos envolvendo inseminação artificial, como palpação retal e contaminação por luvas, podem transmitir altas cargas virais pela mucosa retal. A monta natural foi um fator de proteção neste estudo.…”
Section: Discussionunclassified
“…The study, conducted between 2006 and 2007, involved 1,527 dairy cows on 11 commercial dairy herds in Chile ( 1 ). Farms were selected based on background information obtained from a previous BLV study in Southern Chile that had sampled infected farms ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples (6 mL) were collected from the medium coccygeal vein via venipuncture, 3 mL was collected in EDTA tubes to perform the WBC and smears, and 3 mL collected in a tube without EDTA to obtain the serum of each animal, then refrigerated until they arrived at a designated laboratory at the Universidad Austral de Chile. Blood samples were centrifuged, and the serum samples were identified with a unique numeric code and stored in Eppendorf tubes at −20C until further processing ( 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BLV is transmitted either horizontally or vertically through the transfer of biological fluid contaminated with lymphocytes containing the BLV provirus integrated into the host genome DNA, such as blood and saliva [1,2]. Previous studies have also reported that BLV infection is transmitted through the biting of blood-sucking flies such as those in the Tabanidae family [3] and is related to practices such as breeding by natural service [4] or artificial insemination [5].…”
Section: Introductionmentioning
confidence: 99%